2023
DOI: 10.1029/2022rs007592
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Orbital Angular Momentum Antennas for Target Localization

Abstract: The exploitation of Orbital Angular Momentum (OAM) is proposed to design circular‐support continuous aperture distributions and concentric‐ring arrays for target‐localization applications. The proposed approach allows generating a single isolated null of the field in the target direction, which is of interest with respect to common techniques leading to a line (or perpendicular lines) of power‐pattern zeroes in the spectral plane. In the presented design procedure, the optimal continuous aperture source is fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In fact, Equation 3a follows the rules in , Bucci, Isernia, Morabito, Perna, and Pinchera (2009) where it is shown that the optimal aperture distribution for a pencil beam with maximum directivity is real, Equation 3b complies with (Battaglia et al, 2023b), and Equations 3c and 3d allow generating, by virtue of the symmetry of the array layout, the two difference patterns (Rocca & Morabito, 2015). It is worth noting that a-priori choosing the excitation phases is strictly required in order to make "convex" the constraints on excitation amplitudes which, in turn, is necessary in order to enable the optimal synthesis of phase-only reconfigurable arrays.…”
Section: Statement and Optimal Solution Of The Synthesis Problemmentioning
confidence: 94%
See 4 more Smart Citations
“…In fact, Equation 3a follows the rules in , Bucci, Isernia, Morabito, Perna, and Pinchera (2009) where it is shown that the optimal aperture distribution for a pencil beam with maximum directivity is real, Equation 3b complies with (Battaglia et al, 2023b), and Equations 3c and 3d allow generating, by virtue of the symmetry of the array layout, the two difference patterns (Rocca & Morabito, 2015). It is worth noting that a-priori choosing the excitation phases is strictly required in order to make "convex" the constraints on excitation amplitudes which, in turn, is necessary in order to enable the optimal synthesis of phase-only reconfigurable arrays.…”
Section: Statement and Optimal Solution Of The Synthesis Problemmentioning
confidence: 94%
“…This is done by setting the values of M, Δρ, and Δϕ according to the requirements in terms of array size and overall number of elements, and also by taking into account some desired parameters for the different radiation patterns as, for instance, their beamwidth or divergence angle. Then, we choose the most suitable order of the OAM vortex, say 𝐴𝐴 l𝓁 , by following the guidelines in Battaglia et al (2023b) and perform an uniform discretization of the spectral variables as…”
Section: Statement and Optimal Solution Of The Synthesis Problemmentioning
confidence: 99%
See 3 more Smart Citations